“A Currency of Happenstance” - Louise Owen (Lateral)
Commissioned by Manchester International Festival, The Find (2023) was a participatory art project by conceptual artist Ryan Gander. It distributed non-monetary coin in public space to create what Gander termed “a currency of happenstance,” engaging chance procedures and choice. This essay discusses The Find’s participatory aesthetics and ethical claims, asking what its engagement with coin might elucidate regarding continuities and changes in cultural and economic life, and contemporary political struggles regarding money.